Civic power rebuilding American democracy in an era of crisis - Rahman, K. Sabeel 1983-; Gilman, Hollie Russon ca. 20./21. Jh (Cambridge University Press, 2019)
What will it take to restore American democracy and rescue it from this moment of crisis? Civic Power argues that the current threat to US democracy is rooted not just in the outcome of the 2016 election, but in deeper, systemic forms of inequality that concentrate economic and political power in the hands of the few at the expense of the many. Drawing on historical and social science research and case studies of contemporary democratic innovations across the country, Civic Power calls for a broader approach to democracy reform focused on meaningfully redistributing power to citizens. It advocates for both reviving grassroots civil society and novel approaches to governance, policymaking, civic technology, and institutional design - aimed at dismantling structural disparities to build a more inclusive, empowered, bottom-up democracy, where communities and people have greater voice, power, and agency